5
$\begingroup$

$$ f_{n}(x) = \underbrace{\sqrt{x+\sqrt{x+ ...+ \sqrt{x}}}}_{n} \quad \quad \lim_{n\to\infty} \sum^{n}_{r=1}\frac{1}{2^{r}}\prod^{r-1}_{i=0}\frac{1}{f_{n-i}(x)} = \frac{1}{2f_{\infty}(x)-1} $$

I produced the left hand side by examining the pattern of the derivatives of $\, f_{n}(x)$ and the right hand side by using the property of $\, f_{\infty}(x)$ that: $\, f_{\infty}(x)=\sqrt{x + f_{\infty}(x)}$ and differentiating. I have no idea how to prove such a thing, nor do I know how to prove the general formula of the derivate (EDIT: I have now proved the general formula of the derivative but am still stumped by the limit problem!):

$$_{m}f_{n}(x) = \underbrace{\sqrt[m]{x+\sqrt[m]{x+ ... + \sqrt[m]{x}}}}_{n} \quad \quad _{m}f_{n}'(x) = \sum^{n}_{r=1}\frac{1}{m^{r}} \prod^{r-1}_{i=0} (f_{n-i}(x))^{1-m}$$

Obviously given my second formula, I could generalise the first equality but, I thought the case $m=2$ came out quite nicely.

One last thing, is there any nicer notation I can use for the function rather than writing it out with the underbrace and whatnot?

Edit: Just realised I didn't mention it at all in the original post, the right-hand side is the infinite sum of a geometric progression:

$$\sum^{\infty}_{r=1}\bigg(\frac{1}{2f_{\infty}(x)}\bigg)^{r} = \frac{1}{2f_{\infty}(x)-1} $$

So the question can be rephrased as proving:

$$\lim_{n\to\infty} \sum^{n}_{r=1}\frac{1}{2^{r}}\prod^{r-1}_{i=0}\frac{1}{f_{n-i}(x)} = \sum^{\infty}_{r=1}\bigg(\frac{1}{2f_{\infty}(x)}\bigg)^{r}$$

Which seems intuitively true but, I do not know how to prove it rigorously.

$\endgroup$
  • $\begingroup$ Can you explain the meaning of $f_\infty (x)$ ? $\endgroup$ – S.H.W Jun 8 '17 at 0:31
  • $\begingroup$ @S.H.W it is an infinite radical of x's $\endgroup$ – Joshua Farrell Jun 8 '17 at 14:15
2
+50
$\begingroup$

It took me a while to see how you managed to find that formula, but indeed when you define

$$ _mf_n(x) = (x + {_mf_{n-1}}(x))^{1/m} $$

with $f_{n} = 0$ for $n \leq 0$, then it follows that

$$ _mf'_n(x) = \frac1m(x + {_mf'_{n-1}}(x))^{1/m - 1} (1 + {_mf'_{n-1}}(x)) = \frac1m(_mf_n(x))^{1 - m} (1 + {_mf'_{n-1}}(x)) $$

and through induction you can then show that

$$ _{m}f_{n}'(x) = \sum^{n}_{r=1}\frac{1}{m^{r}} \prod^{r-1}_{i=0} (_mf_{n-i}(x))^{1-m}. $$

actually if we let $(_mf_{n}(x))^{1-m} = 0$ for $n \leq 0$ then we can make our lives slightly easier by writing this as

$$ _{m}f_{n}'(x) = \sum^{\infty}_{r=1}\frac{1}{m^{r}} \prod^{r-1}_{i=0} (_mf_{n-i}(x))^{1-m}. $$

If we now let $_mf_{\infty}(x) = \lim_{n \to \infty} {_mf_n}(x)$ then we can show that for any $r$

$$ \lim_{n\to\infty} \frac{1}{m^{r}} \prod^{r-1}_{i=0} (_mf_{n-i}(x))^{1-m} = \left(\frac{(_mf_{\infty}(x))^{1-m}}{m} \right)^{r} $$

as long as $_mf_{\infty}(x)$ exists.

We can also show that $_mf_{n}(x)$ is monotonically increasing in $n$. Note that for all $x > 0$ we have ${_mf_{1}}(x) = x^{1/m} > 0 = {_mf_{0}}(x)$ and if $$ {_mf_{n}}(x) \geq {_mf_{n-1}}(x) $$ then $$ {_mf_{n+1}}(x) = (x + {_mf_{n}}(x))^{1/m} \geq (x + {_mf_{n-1}}(x))^{1/m} = {_mf_{n}}(x) $$ so ${_mf_{n}}(x)$ is always monotonically increasing for $x>0$. This allows us to use the monotone convergence theorem to conclude that for all $x>0$

$$ \begin{align} \lim_{n\to\infty} \sum^{\infty}_{r=1}\frac{1}{m^{r}} \prod^{r-1}_{i=0} (_mf_{n-i}(x))^{1-m} &= \sum^{\infty}_{r=1} \lim_{n\to\infty} \frac{1}{m^{r}} \prod^{r-1}_{i=0} (_mf_{n-i}(x))^{1-m}\\ &= \sum^{\infty}_{r=1} \left(\frac{(_mf_{\infty}(x))^{1-m}}{m} \right)^{r}\\ &= \frac{1}{1 - \frac{(_mf_{\infty}(x))^{1-m}}{m}} - 1\\ &= \frac{(_mf_{\infty}(x))^{1-m}}{(_mf_{\infty}(x))^{1-m} - m} \end{align} $$

setting $m=2$ results in the special case you found.

You could also try to prove this by showing

$$ \lim_{n\to\infty} \lim_{h\to0} \frac{_{m}f_{n}(x+h) - {_{m}f_{n}(x)}}{h} = \lim_{h\to0} \lim_{n\to\infty} \frac{_{m}f_{n}(x+h) - {_{m}f_{n}(x)}}{h} $$

but showing that you're allowed to exchange the two limits is a bit involved, especially with no idea what the function looks like. So using the expression you found for $_{m}f_{n}'(x)$ might well be the easiest approach.

$\endgroup$
  • $\begingroup$ Very much liked the trick on your fourth line of text. In your fifth line, can you simply let them equal each other? Since if n tends to infinity, surely i also tends to infinity, which is the trouble I was having since it equaling geometric progression implies there is never a $_{m}f_{0}(x)$ term surely? $\endgroup$ – Joshua Farrell Jun 8 '17 at 14:15
  • $\begingroup$ In $\frac{1}{m^{r}} \prod^{r-1}_{i=0} (_mf_{n-i}(x))^{1-m}$ the index $i$ only tends to infinity as $r$ tends to infinity, but as long as we keep $r$ fixed there's no problem. Of course this only shows that the terms of the sum converge to that of a geometric series, to show that the sum itself converges requires more care, which is why I needed to show that $_mf_n(x)$ (and by extension $\frac{1}{m^{r}} \prod^{r-1}_{i=0} (_mf_{n-i}(x))^{1-m}$) is monotonically increasing. $\endgroup$ – Contravariant Jun 8 '17 at 14:59

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.